2021
DOI: 10.1111/1750-3841.15889
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting the chemical composition of essential oils from Psidium cattleianum and Psidium guajava and its antimicrobial and antioxidant properties

Abstract: The genus Psidium comprises several native Brazilian plants, such as the araçá and guava trees. They are interesting sources of essential oils (EOs) that can be used as natural preservatives in foods due to their bioactive properties. This work aimed to evaluate and correlate the biological properties of the EOs from araçá and guava leaves with their chemical compounds. The gas chromatography-mass spectrometry (GC/MS) was used to determine the chemical composition of EOs. The antimicrobial activity was tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 74 publications
0
5
0
1
Order By: Relevance
“…On the other hand, only one report was conducted on the EOs from Egyptian species ( Soliman et al, 2016 ). The relevant literature stated that the EOs derived from P. cattleianum leaves possessed significant in vitro antioxidant, antimicrobial, anti-inflammatory, and anticancer activities ( Castro et al, 2015 ; Chrystal et al, 2020 ; de Souza et al, 2021 ). To the best of our knowledge, no prior study has investigated the volatile metabolites from the flowers; hence, it is interesting to investigate the chemical nature of its derived EOs in comparison with those obtained from the leaves, in an attempt, to discover a new active essential oil-based remedy for the management of cancer and inflammatory disorders.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, only one report was conducted on the EOs from Egyptian species ( Soliman et al, 2016 ). The relevant literature stated that the EOs derived from P. cattleianum leaves possessed significant in vitro antioxidant, antimicrobial, anti-inflammatory, and anticancer activities ( Castro et al, 2015 ; Chrystal et al, 2020 ; de Souza et al, 2021 ). To the best of our knowledge, no prior study has investigated the volatile metabolites from the flowers; hence, it is interesting to investigate the chemical nature of its derived EOs in comparison with those obtained from the leaves, in an attempt, to discover a new active essential oil-based remedy for the management of cancer and inflammatory disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The data suggested that using the ABTS •+ assay, we obtained higher values of the antioxidant activity of EOs and HDs compared to DPPH • assay. The different values of the antioxidant activity measured for the same sample (EO or HD) could be explained by the different mechanisms involved in the reactions of radical antioxidant and sample compounds [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, several authors have reported that the main component of the extracts or essential oils of guava leaves is β-Caryophyllene ( 45 , 49 , 50 ), which has recently gained attention due to its potential application for the treatment of various disorders such as cancer, chronic pain, and inflammation ( 51 ). In addition, many of the plant extracts where β-Caryophyllene is found have antimicrobial effects, notwithstanding the role that this compound plays in said activity is still unclear.…”
Section: Phytochemical Compositionmentioning
confidence: 99%
“…On the other hand, the proposed mode of action of β-caryophyllene, a bicyclic sesquiterpene considered by multiple authors as the main component of guava leaf extract ( 45 , 49 , 50 ), is through altering the bacterial membrane permeability and causing non-selective pore formation. This induces the intracellular content leakage leading to damage and loss of the membrane integrity and may eventually lead to cell death ( 52 ).…”
Section: Potential Mechanisms Of Action Of Antimicrobial Activitymentioning
confidence: 99%